Aktualisasi Pembelajaran Berdiferensiasi pada Mata Pelajaran Fikih di Madrasah Tsanawiyah - Alfa Dalila; Fifi Nofiaturrahmah; Siti Malaiha Dewi; Sofiyyah (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study was motivated by the differences in students’ abilities, interests, and learning styles in Fikih learning for students at Madrasah Tsanawiyah. The learning process, which still tended to use lecture-based methods, caused some students to be less active and their learning motivation had not yet reached an optimal level. Therefore, differentiated learning was implemented as an effort to adjust the learning process to students’ learning needs. This study aimed to analyze the implementation of differentiated learning in the Fikih subject and to identify its supporting and inhibiting factors. The research employed a qualitative approach with a descriptive case study design. The research subjects consisted of the headmaster, Fikih teacher, vice principal of curriculum affairs, and eighth-grade students. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results showed that the implementation of differentiated learning had been conducted through planning, implementation, and evaluation stages by considering students’ needs, interests, and abilities. Teachers applied various learning methods such as discussions, practical activities, question-and-answer sessions, and the use of diverse learning media. Supporting factors included good communication, teacher readiness, learning facilities, and student enthusiasm. Meanwhile, inhibiting factors included limited time, differences in students’ abilities, and classroom management constraints. Nevertheless, differentiated learning was able to improve students’ activeness and learning motivation in the Fikih subject.